Infant Birth Weight in Mothers with Maternal Anemia at Dupak Public Health Center Surabaya Working Area in 2017 - Marisabell Giovanni; Gwenny Ichsan Prabowo; Widati Fatmaningrum (Biomolecular and Health Science Journal, 2019)
Introduction: Anemia in pregnant women is a factor that directly affects the incidence of LBW and can be measured to determine nutritional status during pregnancy. This research is to determine the association of infant birth weight in mothers with maternal anemia at Public Health Center working area in Surabaya.Methods: This research was a cross-sectional approach The sample of this research were 75 pregnant women at Dupak Public Health Center in Surabaya City in 2017 taken by total sampling technique. The data used was taken from the 2017 mother cohort book.Results: The incidence of LBW at Dupak Public Health Center Surabaya working area in 2017 was 12 people (16%). The incidence of anemia at Dupak Public Health Center Surabaya working area in 2017 was 38 people (50.7%). The correlation between LBW and anemia in pregnancy using Chi-Square was p = 0.496.Conclusion: There was no correlation between maternal anemia and LBW There are other factors that can affect the incidence of LBW, such as body weight and maternal height, the number of parity, a short pregnancy distance, and the existence of problems in the history of previous pregnancy and childbirth.